Europe in crisis : intellectuals and the European idea, 1917 - 1957 - Hewitson, Mark Hrsg; D'Auria, Matthew BeteiligteR (Berghahn Books, 2012)
The united states of Europe: the European question in the 1920s / Mark Hewitson -- Europe and the fate of the world: crisis and integration in the late 1940s and 1950s / Mark Hewitson -- Inventing Europe and reinventing the nation-state in a new world order / Mark Hewitson -- Richard Nicolaus Coudenhove-Kalergi, founder of the Pan-European Union, and the birth of a "new" Europe / Anita Prettenthaler-Ziegerhofer -- Noble continent? German-speaking nobles as theorists of European identity in the interwar period / Dina Gusejnova -- Imperium Europaeum: Rudolf Pannwitz and the German idea of Europe / Jan Vermeiren -- New middle ages or new modernity? Carl Schmitt's interwar perspective on political unity in Europe / Ionut Untea -- Rosenzweig, Schmitt and the concept of Europe / Vittorio Cotesta -- From centre to province: changing images of Europe in the writings of Jerzy Stempowski / ?ukasz Miko?ajewski -- Visualizing Europe from 1900 to the 1950s: Identity on the move / Michael Wintle -- Europe and the artistic patrimony of the interwar period: the International Institute for Intellectual Cooperation at the League of Nations / Annamaria Ducci -- Huizinga, the Netherlands and the spirit of Europe, 1933-1945 / Anne-Isabelle Richard -- The idea of European unity in Heinrich Mann's political essays of the 1920s and early 1930s / Ernest Schonfield -- Lucien Febvre and the idea of Europe / Vittorio Dini -- Junius and the president professor: Luigi Einaudi's European Federalism / Matthew D'Auria -- Federate or perish: the continuity and persistence of the federal idea in Europe, 1917-1957 / Michael Burgess -- Conclusion: Europe between a crisis of culture and political regeneration